Enhancing Pokémon VGC Player Performance: Intelligent Agents Through Deep Reinforcement Learning and Neuroevolution - (:unkn) unknown (Springer Nature Switzerland, 2024)
Competitive Pokémon battles demand deep strategic thinking and real-time decision-making, posing challenges for players seeking to optimize their performance. This paper presents a novel approach utilizing Deep Reinforcement Learning and Neuroevolution ...
Keywords: Aprendizaje por refuerzo; Videojuegos